2020
DOI: 10.3389/fclim.2020.00003
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in Rainfall Extremes in the Metropolitan Area of São Paulo: Causes and Impacts

Abstract: This study analyses observed trends in extreme rainfall events in the Metropolitan Area of São Paulo (MASP). Rainfall data sets with more than 60 years of record in MASP are used. In MASP, extreme rainfall events represent hydro meteorological hazards that trigger flash floods and landslides. Changes in rainfall extremes can be partly due to natural climate variability. In addition, it can also be related to global warming and/or urbanization. Total annual precipitation and the number of days with precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 47 publications
2
30
0
8
Order By: Relevance
“…They also analyzed the relationship between the phases of the Southern Annular Mode (SAM) and the position of the SASA. Although the focus of the Marengo et al 2020 [44] was the climate variability impact in a metropolitan city in the ESA, their large-scale analysis clearly shows the humidity flux variability coming from the South Atlantic Ocean toward the region. Changes in the circulation can be important for the increase in the extreme wet and dry events observed in the period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also analyzed the relationship between the phases of the Southern Annular Mode (SAM) and the position of the SASA. Although the focus of the Marengo et al 2020 [44] was the climate variability impact in a metropolitan city in the ESA, their large-scale analysis clearly shows the humidity flux variability coming from the South Atlantic Ocean toward the region. Changes in the circulation can be important for the increase in the extreme wet and dry events observed in the period.…”
mentioning
confidence: 99%
“…Attribution studies to identify whether the increase in the frequency of the wet and dry events registered during the 1980-2018 period over the ESA are due to natural or anthropogenic causes are still being developed. However, some possible physical explanation was given by Marengo et al 2020 [44]. They found that changes in the position and intensity of the SASA are responsible for changes in the atmospheric circulation in the ESA.…”
mentioning
confidence: 99%
“…The 3rd International Electronic Conference on Atmospheric Sciences (ECAS 2020), 16-30 November 2020; Sciforum Electronic Conference Series, Vol. 3, 2020 of consecutive dry days also observed in MASP [8] indicates that intense precipitation is concentrated in fewer days, separated by longer dry spells.…”
Section: Introductionmentioning
confidence: 74%
“…In the last decade, the 2014 drought over Southeastern Brazil affected the water supply in the Metropolitan Area of Sao Paulo (MASP), one of the most populous areas in South America [3]. On the other hand, the observed positive trend in the frequency and intensity of extreme rainfall events in MASP, particularly during the austral Summer, triggers flash floods and landslides over the area [7,8]. The increasing number…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation